2016
DOI: 10.1002/1873-3468.12456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the interaction domains between α‐ and γ‐subunits of GlcNAc‐1‐phosphotransferase

Abstract: The disease-associated hexameric N-acetylglucosamine (GlcNAc)-1-phosphotransferase complex (α β γ ) catalyzes the formation of mannose 6-phosphate residues on lysosomal enzymes required for efficient targeting to lysosomes. Using pull-down experiments and mutant subunits, we identified a potential loop-like region in the α-subunits comprising residues 535-588 and 645-698 involved in the binding to γ-subunits. The interaction is independent of the mannose 6-phosphate receptor homology domain but requires the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition, there are four so-called spacer domains in the α/β precursor whose functions are beginning to be elucidated. Thus, we have reported that spacer-1 (residues 86–322) determines the site of cleavage of the α/β precursor and serves to limit the phosphorylation of non-lysosomal glycoproteins, 13 whereas spacer-2 contains the γ-subunit binding site 12, 14. Besides these domains, the α and β subunits also harbor four Stealth domains that together form the catalytic core of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are four so-called spacer domains in the α/β precursor whose functions are beginning to be elucidated. Thus, we have reported that spacer-1 (residues 86–322) determines the site of cleavage of the α/β precursor and serves to limit the phosphorylation of non-lysosomal glycoproteins, 13 whereas spacer-2 contains the γ-subunit binding site 12, 14. Besides these domains, the α and β subunits also harbor four Stealth domains that together form the catalytic core of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…In the Golgi apparatus the α/β‐precursor is proteolytically cleaved into enzymatically active α‐ and β‐subunits by site‐1 protease (S1P; Figure a; Marschner, Kollmann, Schweizer, Braulke, & Pohl, ; Velho et al, ). The soluble γ‐subunit directly binds to the α‐subunit and enhances the GlcNAc‐1‐phosphotransferase activity for M6P modification of specific lysosomal enzymes (De Pace et al, ; Di Lorenzo et al, ; Velho, De Pace, Tidow, Braulke, & Pohl, ).…”
Section: Background and Biological Significancementioning
confidence: 99%
“…Noteworthy, by using a recombinant lysosomal enzyme instead of the artificial substrate, the GlcNAc‐1‐phosphotransferase activity has been shown to be strongly reduced, demonstrating that both Notch repeat‐like and DMAP domains are involved in the binding to lysosomal enzymes (Qian et al, ; Qian, Flanagan‐Steet, van Meel, Steet, & Kornfeld, ; van Meel et al, ). In addition, GNPTAB missense mutations in the γ‐subunit‐binding domain decrease the GlcNAc‐1‐phosphotransferase activity (Figure b), presumably by impairing the interaction between the α‐ and γ‐subunits and consequently the subunit assembly of the complex (De Pace et al, ; Velho, De Pace, et al, ). Likewise, loss‐of‐function mutations in GNPTG cause a significant reduction in enzymatic activity (De Pace et al, ; Di Lorenzo et al, ).…”
Section: Genotype‐phenotype Correlationsmentioning
confidence: 99%
“…It has been suggested that the ␥-subunits enhance the recognition and M6P formation of distinct lysosomal enzymes by the ␣and ␤-subunit (11,12), whereas other studies failed to show direct interactions of the ␥-subunits with lysosomal enzymes (6,13). Recently, we identified the ␥-subunit binding domain in a previously uncharacterized luminal region of the ␣-subunit required for maximum Gl-cNAc-1-phosphotransferase activity (14,15).…”
mentioning
confidence: 96%